1995
DOI: 10.1152/jn.1995.74.2.802
|View full text |Cite
|
Sign up to set email alerts
|

Relation between cerebral activity and force in the motor areas of the human brain

Abstract: 1. Positron emission tomography (PET) studies were performed in six normal right-handed male volunteers (age 30 +/- 3) to investigate the relationship between cerebral activation as measured by relative regional cerebral blood flow (rCBF) and force peak exerted during right index finger flexion. The purpose was to determine in which central motor structures activity is directly correlated with force for repeatedly executed movements. 2. Twelve PET rCBF measurements were performed in each volunteer with the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
244
1
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 429 publications
(290 citation statements)
references
References 0 publications
41
244
1
2
Order By: Relevance
“…These findings about OxyHb are similar to other studies showing that finger force is correlated with brain activity [1][2][3]. And DeoxyHb did not fall in group analysis, it is explained by the results of a study which imply the possibility of the deoxyHb is not necessarily shown decrease in brain activity [10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings about OxyHb are similar to other studies showing that finger force is correlated with brain activity [1][2][3]. And DeoxyHb did not fall in group analysis, it is explained by the results of a study which imply the possibility of the deoxyHb is not necessarily shown decrease in brain activity [10].…”
Section: Discussionsupporting
confidence: 88%
“…These include the primary sensorimotor cortex, the premotor area, the pre-supplementary motor area (pre-SMA), the supplementary motor area (SMA), and the prefrontal area. Studies have investigated these motor-related areas, and the influence of finger force on brain activity [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Activity changes within cingulate sulcal areas were thus similar to those observed in primary motor areas. Movement-related activity in caudal cingulate cortex cells in monkeys (Shima et al 1991), close anatomical connections between cingulate motor areas and primary motor cortex again in monkeys (Muakkassa and Strick 1979;Dum and Strick 1991) and a covariation of rCBF levels in cingulate sulcal areas and primary sensorimotor area during force control in humans (Dettmers et al 1995) support the notion that caudal cingulate areas are involved in elementary processes of movement control in monkeys and humans. Why, then, did we not observe a further increase in cingulate activity during bimanual in-phase movements over and above that which would be expected from the combined unimanual conditions, even though the actual movement execution now has to be coordinated between both sides?…”
Section: Ventral Medial Wall Areasmentioning
confidence: 52%
“…There was no local maximum in the pre-central region. In comparison, in recent studies of motor activity there are local maxima in the pre-central region or in the central sulcus (Dettmers et al, 1995;Stephan et al, 1995;Fink et al, 1997).…”
Section: Discussionmentioning
confidence: 80%